2017
DOI: 10.1016/j.neuron.2017.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Functional Convergence at the Retinogeniculate Synapse

Abstract: Summary Precise connectivity between retinal ganglion cells (RGCs) and thalamocortical (TC) relay neurons is thought to be essential for the transmission of visual information. Consistent with this view, electrophysiological measurements have previously estimated that 1–3 retinal ganglion cells (RGCs) converge onto a mouse geniculate TC neuron. Recent advances in connectomics and rabies tracing have yielded much higher estimates of retinogeniculate convergence, although not all identified contacts may be funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 47 publications
4
82
0
Order By: Relevance
“…This revealed a striking, ß30-fold difference in the unitary synaptic conductances between inhibition and excitation converging onto LSO neurons, at least when excitation and inhibition are both measured under conditions of high driving forces (ß70 mV). The minimal optogenetic stimulation method used here might also be useful for measuring the strength of unitary synaptic events in other circuits (see also Lu & Trussell, 2016;Litvina & Chen, 2017).…”
Section: Strong But Variable Unitary Inhibition Onto Lso Neuronsmentioning
confidence: 99%
“…This revealed a striking, ß30-fold difference in the unitary synaptic conductances between inhibition and excitation converging onto LSO neurons, at least when excitation and inhibition are both measured under conditions of high driving forces (ß70 mV). The minimal optogenetic stimulation method used here might also be useful for measuring the strength of unitary synaptic events in other circuits (see also Lu & Trussell, 2016;Litvina & Chen, 2017).…”
Section: Strong But Variable Unitary Inhibition Onto Lso Neuronsmentioning
confidence: 99%
“…Thus, we cannot safely conclude on the number of inhibitory inputs received by a single LSO neuron based on the present SBEM data. A similar disagreement between the number of optogenetically stimulated synaptic inputs, and the number of inputs found in connectomics studies on the light and electron microscopic level (Morgan et al 2016;Rompani et al 2017), has recently been found at the retinogeniculate synapse (Litvina & Chen, 2017).…”
Section: Technical Considerationsmentioning
confidence: 55%
“…Interestingly, using ontogenetic stimulation of retinal terminals expressing channelrhodopsin (ChR2) Litvina and Chen (Litvina and Chen, 2017) have recently confirmed a higher level functional retinal convergence onto dLGN relay cells. Here, we sought to understand the molecular mechanisms underlying this newly appreciated convergence in visual thalamus.…”
Section: Disscussionmentioning
confidence: 96%